1999
DOI: 10.1073/pnas.96.16.9118
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of primitive human hematopoietic progenitors on the basis of aldehyde dehydrogenase activity

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
413
0
7

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 483 publications
(433 citation statements)
references
References 38 publications
8
413
0
7
Order By: Relevance
“…Thus, ALDH1A1-expressing cells have a crucial role in the initiation and progression of esophageal squamous cell carcinoma. ALDH1A1 is a predominant isoform of aldehyde dehydrogenase family in mammals located in the cytoplasm 15,16 and is originally considered as a marker for normal hematopoietic progenitor cells, 17 and is also found in cancer cells with stem cell property, that is, cancer stem-like cells, in several malignant tumors including leukemia, 9 breast cancer 7 and lung cancer. 8,18 Wang et al 19 reported that ALDH1A1 was located in the nuclei of esophageal squamous cell carcinoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, ALDH1A1-expressing cells have a crucial role in the initiation and progression of esophageal squamous cell carcinoma. ALDH1A1 is a predominant isoform of aldehyde dehydrogenase family in mammals located in the cytoplasm 15,16 and is originally considered as a marker for normal hematopoietic progenitor cells, 17 and is also found in cancer cells with stem cell property, that is, cancer stem-like cells, in several malignant tumors including leukemia, 9 breast cancer 7 and lung cancer. 8,18 Wang et al 19 reported that ALDH1A1 was located in the nuclei of esophageal squamous cell carcinoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…Such cells, called label-retaining cells [5,6], can now be purified out live in genetic models and used in functional assays [1]. Finally, stem cells can be enriched using the side population (SP) [7] and Aldefluor [8] assays, both of which take advantage of the preferential expression of detoxification molecules (e.g., ABC transporters such as ABCG2 in SP analysis) or enzymes (e.g., ALDH1A1 in Aldefluor assay) in adult stem cells. …”
Section: Heterogeneity Of Normal Stem/progenitor Cellsmentioning
confidence: 99%
“…The ALDEFLUOR (Stem Cell Technologies, Grenoble, France, http://www.stemcell.-com) technique has recently been developed to quantify ALDH activity level in viable cells [15,16]. Using ALDE-FLUOR BODIPY (4,4-difluoro-5,7-dimethyl-4-bora-3a,4a-diaza-5-proprionic acid)-aminoacetaldehyde (BAAA), a fluorescent synthetic substrate of ALDH, it is possible to isolate HSCs/HPCs using fluorescence-activated cell sorting (FACS) [17][18][19][20]. Similar to the SP phenotype, the ALDH activity level is considered as a stem cell marker because it is expressed in stem cells from several tissues, including hematopoietic, keratocytic, mesenchymal, neuronal, and endothelial stem cells [21,22].…”
Section: Introductionmentioning
confidence: 99%